Effect of breast feeding on child development: At birth and beyond - Tasnim, Saria (South East Asia Journal of Public Health, 2015)
The effect of breast feeding on infant health and development has been the subject of scientific enquiry for decades. The association between breast feeding and early child development is also a complex issue. It has been found that determining the true influence of breastfeeding on child development is difficult for several reasons. This review has been made to explore the effect of ever breast feeding and duration of breast feeding on intelligent quotient, psychomotor and social development of the child during childhood and beyond. Breast feeding has positive effects on cognitive development of infant and it is more pronounced in premature infants. Breast feeding infants have higher intelligence quotient (IQ) than non-breast fed. The amount of mutual touch, tactile stimulation and mothers gaze to the infant are significantly elevated during breastfeeding and this has a positive influence on the childs psychological development. The impact of breast feeding on cognitive development, behavior, social adaptation and understanding of the infant needs to be emphasized during the promotion of breast feeding and early child development programs. DOI: http://dx.doi.org/10.3329/seajph.v4i1.21831 South East Asia Journal of Public Health Vol.4(1) 2014: 4-8